Scheduling Critical Activities of Stochastic Projects Management - احمد علاء الدين نوري; ابراهيم نذير عباس (Journal of Economics and Administrative Sciences, 2012)
In this paper, we consider the problem of stochastic project network when some or all activities are interrupted. An approach has been built to schedule the critical activities, by constructing some expressions based on the project lateness costs due to the interruption activities. Two simple example are presented to validate our approach. Key words: Project Management, Project scheduling, Stochastic activity duration, Stochastic PERT. Introduction Recently, Projects planning and optimal timing, under uncertainty are extremely critical for many organizations, see [19]. Having an effective mathematical model will give project managers a significant tool for replanning projects allocation decisions in response events and outcomes. As a result, the uncertainty associated with such risky projects should be reduced. No one factor can account for, or prevent, failure in a project. It is common practice for a project team to develop a comprehensive risk assessment and risk management plan. Identifying the most critical activities with regard to schedule risk is a problem faced by all project managers. The problem of identifying critical activities (CA) in a deterministic network is well understood, by standard Critical Path Method (CPM) known as Program Evaluation and Review Technique (PERT). Since a project could be delayed if these activities were not completed in the scheduled time. The classical PERT method is the probably is the best-known mechanism for considering the stochastic nature of activity durations, in which it is possible to develop estimates of the uncertainty of the project make span. For more details see [8] & [10 ].